Short-run evaluation of NExTWORK - Roantree, Barra; Krutikova, Sonya; Tahir, Imran (Institute for Fiscal Studies, 2025)
This report presents findings from a randomised controlled trial (RCT) evaluating NExTWORK, a new active labour market programme developed by the ROCKWOOL Foundation in partnership with stakeholders including Roskilde Municipality. The programme is designed to improve the educational and economic outcomes of disadvantaged young people receiving social assistance in Denmark. Using a combination of administrative register, municipality, and programme data, it assesses the effectiveness of the programme relative to the existing system of supports over a 2.5 year (130 week) time horizon.
PUBLISHED
Keywords: Inclusive Society